Frequency selective surface analysis and design - Vardaxoglou, John C. (Antennas series, 1997)
Frequency Selective Surfaces (FSS) play a key role in many antenna systems for modern fixed and mobile communication systems. Such important practical applications have resulted from research into FSS and related array topics undertaken in both the industrial and academic sectors in recent years. This book draws together the multifaceted work on FSS and provides a modern overview of the underlying theory and mathematical formalism. Step-by-step accounts of analysis techniques, numerical considerations and FSS designs are given. The book is divided into two complementary parts, which differ in their approach to the analysis of FSS but produce the same results. Part I is based on the 'field approach' where the analysis uses modal expansions of vector electric and magnetic fields. The second part is contributed by Dr R Orta and Dr R Tascone of Politecnico di Torino, Italy, whose framework for the FSS analysis is a modal transmission line description of wave propagation. The terminology and definitions employed in the latter approach are more geared to readers who are familiar with electrical networks and transmission line theory.